Effect of structural and dynamical properties of lipid bilayer on water permeation studied using course-grained molecular dynamics simulation - Enriquez, John Isaac (Animo Repository, 2017)
© 2017 IEEE. The greatest challenge in commercialization of microalgae products is the reduction of the overall cost of extraction. An understanding of the exact mechanism of water permeation across cell membrane will improve the current extraction methods and may possibly lead to the development of new technology. Molecular dynamics calculations using GROMACS software and MARTINI force field were performed to study how temperature affects the structural and dynamical properties of DPPC lipid bilayer. In general, the area per lipid and diffusion constant increases with temperature, while the bilayer thickness decreases. Water permeation simulations were conducted by accelerating the water molecules on one side of the bilayer towards the direction of the opposite side, creating pressure difference comparable to osmotic pressure. At 325 K, a pressure difference of 36.9 MPa (369 bar) induces water permeation after 5.2 ns simulation time. Simulation at higher temperatures requires lower pressure difference for water permeation. The results suggest that the temperature induced changes in the area per lipid, bilayer thickness, and lateral diffusion constant affect the water permeability on lipid membrane.